2007
DOI: 10.1051/0004-6361:20066899
|View full text |Cite
|
Sign up to set email alerts
|

Closed-form expressions for particle relative velocities induced by turbulence

Abstract: In this note we present complete, closed-form expressions for random relative velocities between colliding particles of arbitrary size in nebula turbulence. These results are exact for very small particles (those with stopping times much shorter than the large eddy overturn time) and are also surprisingly accurate in complete generality (that is, also apply for particles with stopping times comparable to, or much longer than, the large eddy overturn time). We note that some previous studies may have adopted pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
509
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 427 publications
(525 citation statements)
references
References 10 publications
14
509
2
Order By: Relevance
“…We therefore focus on the intermediate velocity regime. In particular, the relative velocity between two equal solid spheres of 1 < τ 0 /t s < Re 1/2 is (Ormel & Cuzzi 2007) , where n d is the dust number density and R gd = 100 is the standard gas-to-dust density ratio by mass.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We therefore focus on the intermediate velocity regime. In particular, the relative velocity between two equal solid spheres of 1 < τ 0 /t s < Re 1/2 is (Ormel & Cuzzi 2007) , where n d is the dust number density and R gd = 100 is the standard gas-to-dust density ratio by mass.…”
Section: Discussionmentioning
confidence: 99%
“…Then, the surface area-to-mass ratio of the dust particles is of critical importance since this quantity determines the amount of coupling between the dust particles and the gas. We use the analytic approximations of Ormel & Cuzzi (2007) for the relative velocity between two particles. These expressions only include contributions that arise as a result of the particle's inertia in a turbulent velocity field and do not contain contributions that arise from gyroresonance acceleration (see, e.g., Yan et al 2004).…”
Section: Working Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…For protoplanetary disks, u col is not determined as simply as that for debris disks. Collisions between small particles have u col u col,crit , while u col is close to u col,crit for collisions with large particles (e.g., Ormel & Cuzzi 2007).…”
Section: Total Ejecta Massmentioning
confidence: 97%
“…We have used a simple analytical model derived by Blum (2004), and checked by Ormel et al (2009), who compared it with their Monte Carlo simulation and demonstrated it is valid for average molecular cloud conditions, with densities of 10 5 cm −3 , temperature of 10 K, and at intermediate velocity regimes 2 (Ossenkopf 1993;Ormel et al 2009;Ormel & Cuzzi 2007). The analytical model is based on the assumption of a monodisperse distribution of spherical particles.…”
Section: A Simple Analytical Modelmentioning
confidence: 99%